Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.18632/oncotarget.20148
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of target genes of spinal cord in different itch models compared with capsaicin assessed by RT-qPCR validation

Abstract: Spinal cord plays a central role in the development and progression of pathogenesis of obstinate pruritus. In the current study, four groups of adult male C57Bl/6 mice were investigated; one group treated with saline, while the other groups intradermally injected with compound 48/80, histamine, α-Me-5-HT and capsaicin (algogenic substance), respectively. The intradermal microinjection of pruritic and algogenic compound resulted in a dramatic increase in the itch/algogenic behavior. Analysis of the microarray d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…It is well known that regulations of gene expression are varied over the time course (64)(65)(66). Our previous research associated with Itchy E3 ubiquitin protein ligase demonstrated that gene expression was significantly different in the C5-C8 spinal cord at 0.5 and 2 h following compound 48/80 injection when compared with the control group (36). Similar to the above method, we also screened key genes in myocardial tissues under 30 min cardiac ischemia following 2 h reperfusion compared with the sham group (67).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It is well known that regulations of gene expression are varied over the time course (64)(65)(66). Our previous research associated with Itchy E3 ubiquitin protein ligase demonstrated that gene expression was significantly different in the C5-C8 spinal cord at 0.5 and 2 h following compound 48/80 injection when compared with the control group (36). Similar to the above method, we also screened key genes in myocardial tissues under 30 min cardiac ischemia following 2 h reperfusion compared with the sham group (67).…”
Section: Discussionmentioning
confidence: 96%
“…Then the rats were quickly decapitated to limit animal suffering and minimize the effects on the experimental results, and the T1-T4 spinal cord segments were immediately removed and frozen with liquid nitrogen for 1 min, then stored at -80˚C until required. Total RNA from each animal was quantified using a mirVana miRNA Isolation kit (Ambion; Thermo Fisher Scientific, Inc., Waltham, MA, USA), and RNA integrity was assessed according to the manufacturer's protocol, which included standard denaturing agarose gel electrophoresis (35)(36)(37). For RNA-seq, the microarray work was performed by CapitalBio Technology Co. Ltd. (Beijing, China), whereby 6 tissue samples (3 model group samples and 3 control group samples) were used for mRNA and lncRNA microarray analysis (38).…”
Section: Tissue Preparation and Microarray Gene Expression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid advancements in high-throughput technologies and computational frameworks offer an excellent opportunity to quantify spinal nociception using neuronal activation induced by noxious stimuli. The author's previous study showed that transcriptomics and metabolomics enable the examination of spinal biological systems in unprecedented detail (32)(33)(34)(35)(36). More recently, different patterns were revealed in the metabolic and transcriptional levels of the thoracic spinal cord under myocardial ischemia-reperfusion injury (37)(38)(39).…”
Section: Quantitative Proteomics Reveal the Alterations In The Spinalmentioning
confidence: 99%
“…Recently, long non-coding RNAs (lncRNAs) have become an increased research focus that plays critical roles in many biological processes [15][16][17][18][19][20]. Recent studies suggest that lncRNAs are often accompanied by important regulatory functions in the heart [21][22][23].…”
Section: Introductionmentioning
confidence: 99%